Electroconvulsive therapy modulates loudness dependence of auditory evoked potentials: a pilot MEG study - Dib, Michael; Lewine, Jeffrey David; Abbott, Christopher C.; Deng, Zhi-De (Frontiers in Psychiatry, 2024)
Introduction Electroconvulsive therapy (ECT) remains a critical intervention for treatment-resistant depression (MDD), yet its neurobiological underpinnings are not fully understood. This pilot study aims to investigate changes in loudness dependence of auditory evoked potentials (LDAEP), a proposed biomarker of serotonergic activity, in patients undergoing ECT. Methods High-resolution magnetoencephalography (MEG) was utilized to measure LDAEP in nine depressed patients receiving right unilateral ECT. We hypothesized that ECT would reduce the LDAEP slope, reflecting enhanced serotonergic neurotransmission. Depression severity and cognitive performance were assessed using the 24-item Hamilton Depression Rating Scale (HDRS24) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), respectively. Results Contrary to our hypothesis, findings indicated a significant increase in LDAEP post-ECT (t8 = 3.17, p = .013). The increase in LDAEP was not associated with changes in depression severity or cognitive performance. Discussion The observed increase in LDAEP suggests a more complex interaction between ECT and neurobiological systems, rather than a direct reflection of serotonergic neurotransmission. Potential mechanisms for this increase include ECT’s impact on serotonergic, dopaminergic, glutamatergic, and GABAergic receptor activity, neuroplasticity involving brain-derived neurotrophic factor (BDNF), and inflammatory modulators such as TNF-α. Our results highlight the multifaceted effects of ECT on brain function, necessitating further research to elucidate these interactions.